## Intermediate Algebra (12th Edition)

$\left\{ -\dfrac{4}{3},0,\dfrac{4}{3} \right\}$
$\bf{\text{Solution Outline:}}$ Express the given equation, $9x^3=16x ,$ in factored form. Then use the Zero Product Property by equating each factor to zero. Finally, solve each of the resulting equations. $\bf{\text{Solution Details:}}$ Using the properties of equality, the given equation is equivalent to \begin{array}{l}\require{cancel} 9x^3-16x=0 .\end{array} The $GCF$ of the constants of the terms $\{ 9,-16 \}$ is $1$ since it is the highest number that can divide all the given constants. The $GCF$ of the common variable/s is the variable/s with the lowest exponent. Hence, the $GCF$ of the common variable/s $\{ x^3,x \}$ is $x .$ Hence, the entire expression has $GCF= x .$ Factoring the $GCF= x ,$ the expression above is equivalent to \begin{array}{l}\require{cancel} x(9x^2-16)=0 .\end{array} The expressions $9x^2$ and $16$ are both perfect squares and are separated by a minus sign. Hence, $9x^2-16 ,$ is a difference of $2$ squares. Using the factoring of the difference of $2$ squares which is given by $a^2-b^2=(a+b)(a-b),$ the expression above is equivalent to \begin{array}{l}\require{cancel} x(3x+4)(3x-4)=0 .\end{array} Equating each factor to zero (Zero Product Property), then \begin{array}{l}\require{cancel} x=0 \\\\\text{OR}\\\\ 3x+4=0 \\\\\text{OR}\\\\ 3x-4=0 .\end{array} Solving each equation results to \begin{array}{l}\require{cancel} x=0 \\\\\text{OR}\\\\ 3x+4=0 \\\\ 3x=-4 \\\\ x=-\dfrac{4}{3} \\\\\text{OR}\\\\ 3x-4=0 \\\\ 3x=4 \\\\ x=\dfrac{4}{3} .\end{array} Hence, the solutions are $\left\{ -\dfrac{4}{3},0,\dfrac{4}{3} \right\} .$